Healthcare-associated infections and the prescribing of antibiotics in hospitalized patients of the Caribbean Community (CARICOM) states: a mixed-methods systematic review. (April 2021) - Wade, T.; Heneghan, C.; Roberts, N.; Curtis, D.; Williams, V.; Onakpoya, I.
Summary: Background: Healthcare-associated infections (HCAIs) and variation in antibiotic prescribing pose a significant public health challenge in hospitals of low-resource countries. Aim: To critically appraise and synthesize the evidence on HCAI and the prescribing of antibiotics in Caribbean Community (CARICOM) states. Methods: All primary qualitative and quantitative studies that addressed HCAI, and the prescribing of antibiotics in hospitalized patients of CARICOM states were included. Ovid Medline, Embase, Global Health, and regional databases were searched. Risk of bias was assessed using the Mixed Methods Appraisal Tool. Findings were presented in narrative and table formats. Findings: Twenty-one studies met the inclusion criteria for this mixed-methods systematic review (MMSR). Studies were from four different CARICOM states: Trinidad and Tobago, Jamaica, Haiti, and Antigua and Barbuda. Intensive care units (ICUs) had the highest rate of infections (67% over four years). Surgical site infections were discussed by seven studies and ranged from 1.5% to 7.3%. For inpatients with contaminated or infected wounds, rates ranged from 29% to 83%. Empiric and prophylactic therapies were common and inappropriately prescribed. Resources and training for healthcare workers in infection control and antimicrobial stewardship were insufficient. Few qualitative studies existed, so it was not possible to integrate evidence from qualitative and quantitative paradigms. Conclusion: Evidence from CARICOM states shows high rates of HCAI and inappropriately prescribed antibiotics, primarily in ICUs. Disease surveillance, infection control, and antimicrobial stewardship programmes require urgent evidence-based improvements.